Effect of dietary supplementation of biofloc meal on growth and survival of GIFT tilapia - Prabu, E.; Rajagopalsamy, C.B.T; Ahilan, B.; Jeevagan, Jegan Michael Andro; Renuhadevi, M. (Indian Journal of Fisheries, 2018)
A 60 days indoor growth trial was conducted to study the effect of dietary supplementation of biofloc meal on growth and survival of juvenile GIFT tilapia. Four isonitrogenous and isoenergetic experimental diets (32% crude protein) were prepared using biofloc meal at different inclusion levels viz., 0 (T0), 20 (T1), 30 (T2) and 40% (T3). A commercial diet (T4) was used for comparison. The feeding trial was conducted in 15 nos. of 40 l plastic troughs in triplicate, utilising GIFT tilapias weighing an average of 2 g. During the experimental period, water quality parameters were measured and recorded daily. The mean value of water temperature, pH, dissolved oxygen, salinity, ammonia-N, nitrite-N, nitrate-N, hardness and alkalinity recorded in the experimental systems were 28.5Â°C, 8.1, 5.5 ppm, 4.5 ppt, 0.03 ppm, 0.07 ppm, 11 ppm, 630 ppm and 162.5 ppm respectively. Among the biofloc meal enriched diets, diet T1 with 20% biofloc yielded the best results in terms of average body weight gain, feed conversion ratio (FCR), specific growth rate (SGR), protein efficiency ratio (PER) and feed efficiency ratio (FER). The mean body weight gain recorded in T1 was 25.28Â±0.81 g. The results demonstrated that biofloc meal is a potential ingredient that can be incorporated in GIFT tilapia diet at 20% level for better growth performance.